Revitalisasi Ruang Terbuka Hijau bagi Warga di RT. 23 RW. 02 Kecamatan Lebakwangi, Kabupaten Kuningan, Jawa Barat - Arief Nugroho Wibowo; Zainal Arifin; Sri Mardiyati; Nini Adelina Tanamal (AJAD : Jurnal Pengabdian kepada Masyarakat, 2026)
This community service program aims to revitalize a green open space in RT. 23 RW. 02 Lebakwangi District, Kuningan Regency, West Java, to improve environmental quality and strengthen social interaction. The main issues were poor maintenance, limited facilities, and low community participation. A community-based participatory approach was applied, involving residents in planning, implementation, and evaluation. Activities included site cleaning, landscape arrangement, vegetation planting, simple facility construction, and environmental education. The results show improved park quality, increased environmental awareness, and renewed social use of public space. The formation of a community management team supports sustainability. This program demonstrates that collaboration between universities and communities can generate positive environmental and social impacts while improving residents' quality of life